Castianeira furva sp. nov. (Araneae, Corinnidae, Castianeirinae), a new polymorphic ground sac spider from the southern Western Ghats of India - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2015)
The ground-dwelling, ant-mimicking corinnid spider genus Castianeira, with Castianeira rubicunda as type species, was erected by Keyserling (1879). Members of the genus are closely related to the Afrotropical genus Cambalida Simon, 1910 (Haddad 2012a) and are distributed mainly in tropical and temperate regions of the world except for Australia and nearby islands (World Spider Catalog 2015). The genus was revised from the Nearctic Region and south-east Asia (Reiskind 1969 and Deeleman-Reinhold 2001, respectively) and currently includes 126 described species, making it as the largest genus within the family Corinnidae (World Spider Catalog 2015). Even though the genus is rich in species, the validity and placement of majority of the species are still doubtful and questionable. For example, according to Haddad (2012b), many of the Afrotropical species, as well as majority of the species described from India (Haddad, pers. comm.) are misplaced or synonyms of previously described ones (e.g. Haddad 2012a, 2013a). The genus thus will remain as a trash-can until all the species described so far can be revised.